A homogeneous analysis of disks around brown dwarfs - Liu, Y.; Joergens, Viki; Bayo, A.; Nielbock, M.; Wang, H. (Astronomy and astrophysics, 2015)
We re-analyzed the Herschel/PACS data of a sample of 55 brown dwarfs (BDs) and very low mass stars with spectral types ranging from M5.5 to L0. We investigated the dependence of disk structure on the mass of the central object in the substellar regime based on a homogeneous analysis of Herschel data from flux density measurements to spectral energy distribution (SED) modeling.